Experimental Infection and Response to Rechallenge of Alpacas with Middle East Respiratory Syndrome Coronavirus - Crameri, Gary (Emerg Infect Dis, 2016)
We conducted a challenge/rechallenge trial in which 3 alpacas were infected with Middle East respiratory syndrome coronavirus. The alpacas shed virus at challenge but were refractory to further shedding at rechallenge on day 21. The trial indicates that alpacas may be suitable models for infection and shedding dynamics of this virus.